Picophytoplankton Niche Partitioning in the Warmest Oligotrophic Sea - Coello-Camba, Alexandra; Agustí, Susana (Frontiers in Marine Science, 2021)
Pico-sized Synechococcus, Prochlorococcus, and eukaryotes are the dominant photosynthetic organisms in the vast warm and oligotrophic regions of the ocean. In this paper, we aim to characterize the realized niches of the picophytoplanktonic community inhabiting the Red Sea, the warmest oligotrophic sea, which is considered to be a model for the future ocean. We quantify population abundances and environmental variables over several oceanographic surveys, and use stepwise regression, principal-component analysis (PCA), and compositional-data analysis to identify the realized niches of the three picophytoplanktonic groups. Water temperature varied from 21.4 to 32.4 °C within the upper 200-m water column, with the warmest waters being found in the South, where nutrients increased. Synechococcus dominated the biomass, contributing 47.6% to the total picophytoplankton biomass, followed by picoeukaryotes (26.4%) and Prochlorococcus (25.9%), whose proportions contrast significantly with those reported in the subtropical ocean, where Prochlorococcus prevails. There were positive and significant relationships between temperature and the three populations, although these were weak for Prochlorococcus (R2 = 0.08) and stronger and steeper for Synechococcus (R2 = 0.57). The three populations centered their maximum abundances (Lorentzian fits) at similar low nutrient values. Synechococcus were centered close to the surface at 77% of surface PAR and 30.6 °C. The picoeukaryotes were centered at lower light (6.4% surface PAR) and warm waters (30 °C). Prochlorococcus was segregated from the surface waters and centered deep at low light (3.2% surface PAR). Light and temperature were the most influential factors determining the community composition, with Synechococcus dominating 74% of the picophytoplankton biovolume in the warmest (>30 °C) waters. In the warm and mesotrophic southern Red Sea, the moderate abundances of picoeukaryotes and Synechococcus suggest increasing competition with nano and microphytoplankton. Our observations agree with predictions of increasing vertical segregation of picophytoplankton communities with future warming and reveal Synechococcus’s significant capacity to adapt to warming.